Worship as transformational object: Aesthetic experience and the "unthought known" - Dreyer, Yolanda (Stellenbosch theological journal, 2019)
Meaning is formed where an evocative object and the unconscious meet. Such an object can be a thing, a person, a place, art, word, sound or atmosphere. This way of forming meaning does not depend on thinking. Psychoanalyst Christopher Bollas calls it the unthought known. It is a form of knowing that is perceived through imagination - that capacity that mediates between thinking and sensing. The aim of the article is to explore worship as transformational object in discussion with Johan Cilliers' A space for grace: Towards an aesthetics of preaching. In a worship event a rich variety of elements can contribute to aesthetic experience: from space and architecture to art, colour form and symbols, to sound, music and singing, bodily participation, and the spoken word. The article explores how these can function as evocative objects that have the capacity to affect the psyche and transform the self.